A new species of Pterotiltus Karsch (Orthoptera, Acrididae, Oxyinae) from Equatorial Guinea - Charly Oumarou-Ngoute; Hojun Song; Ricardo Mariño-Pérez; Brandon M. Woo; Jackson Linde; C.H.F. Rowell (Journal of Orthoptera Research, 2025)
The genus Pterotiltus Karsch, 1893 currently contains 18 described species. The genus is distributed in West, Central, and East Africa from Ghana to the Congo basin as far as Western Uganda. Pterotiltus bioko sp. nov. is described from specimens recently collected on Bioko Island in Equatorial Guinea. A key to Pterotiltus species is provided.